Redistributive Income Taxation with Directed Technical Change - Jonas Loebbing (ZBW - Leibniz Information Centre for Economics, 2020)
This paper studies the implications of (endogenously) directed technical change for the design of non-linear labor income taxes in a Mirrleesian economy augmented to include endogenous technology development and adoption choices by firms. First, I identify conditions under which any progressive tax reform induces technical change that compresses the pre-tax wage distribution. The key intuition is that progressive tax reforms tend to increase labor supply of less skilled relative to more skilled workers, which induces firms to develop and use technologies that are more complementary to the less skilled. Second, I provide conditions under which the endogenous response of technology raises the welfare gains from progressive tax reforms. Third, I show that directed technical change effects make the optimal tax scheme more progressive, raising marginal tax rates at the right tail of the income distribution and lowering them (potentially below zero) at the left tail. For reasonable calibrations, the directed technical change effects of actual tax reforms on wage inequality appear to be small, but the impact of directed technical change on optimal taxes is considerable. Optimal marginal tax rates increase monotonically over the bulk of the income distribution instead of being U-shaped (as in most of the previous literature) and marginal tax rates on incomes below the median are reduced substantially
Keywords: H21; H23; H24; J31; O33; 330; Optimal Taxation; Directed Technical Change; Endogenous Technical Change; Wage Inequality.